Hubungan Pengetahuan dan Sikap Tentang Bahaya Merokok Dengan Perilaku Merokok Pada Remaja Putra Di SMK N 2 Sukoharjo - Inez Oktavi (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2023)
Smoking behavior is often carried out during adolescence. The number of male students who smoke cigarettes is 38.3%. Lack of knowledge about the dangers of smoking is one of the reasons why teenagers smoke. The aim of this research was to determine the relationship between knowledge and attitudes about the dangers of smoking and smoking behavior among young men at SMK N 2 Sukoharjo, Sukoharjo Regency. This type of quantitative research is an analytical research design with a cross sectional approach.